2011
DOI: 10.1364/josaa.29.000078
|View full text |Cite
|
Sign up to set email alerts
|

Coherence effects in Mie scattering

Abstract: The scattering of a partially coherent beam by a deterministic, spherical scatterer is studied. In particular, the Mie scattering by a Gaussian Schell-model beam is analyzed. Expressions are derived for (a) the extinguished power, (b) the radiant intensity of the scattered field, and (c) the encircled energy in the far field. It is found that the radiant intensity and the encircled energy in the far field depend on the degree of coherence of the incident beam, whereas the extinguished power does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In this section, the TM z and TE z PO σ λ are the shadow and backscatter radiation approximations given by (21) and (17), respectively. The color of the trace indicates l s , i.e., = l a a a 0.2 , 0.5 , 1 s , and 10a.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the TM z and TE z PO σ λ are the shadow and backscatter radiation approximations given by (21) and (17), respectively. The color of the trace indicates l s , i.e., = l a a a 0.2 , 0.5 , 1 s , and 10a.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The pertinent literature on this subject actually deals with the scattering from spheres [21][22][23][24]. There are only two papers known to the author that deal with partially coherent wave scattering from cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral densities are easy to compute using Eqs. (23) and (24), i.e., S i ðρÞ ¼ W ii ðρ; ρÞ. Since the fields are Gaussian distributed, the theoretical correlations of irradiance can be expressed in terms of Eqs.…”
Section: B Enuc and Emgsm Theoretical Csd Matricesmentioning
confidence: 99%
“…Their widespread appeal stems from the fact that, by simply manipulating spatial coherence, the source's resulting shape and polarization can be precisely controlled. Numerous researchers have designed vector partially coherent sources for applications such as free-space and underwater optical communications [7][8][9][10][11][12][13][14][15][16], remote sensing [17,18], optical scattering [19][20][21][22][23][24][25][26][27][28][29], and particle manipulation and trapping [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous published articles exist predicting the polarization, coherence, and beam shape of partially coherent light after propagating through free space and random media [1][2][3][4][5][6][7][8][9][10] or scattering from deterministic and random objects/media. [11][12][13][14][15][16][17][18][19][20][21] Much work has also been performed exploiting coherence to control beam shape [22][23][24][25][26][27][28][29][30] and even as an encoding scheme for holography. 31 Excellent reviews and more in-depth discussions of these topics can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%